Health-related Quality of Life in a Prospective Study of Ultrasound to Detect Cystic Fibrosis–related Liver Disease in Children. Issue 5 (6th September 2022) - Schwarzenberg, Sarah Jane; Palermo, Joseph J.; Ye, Wen; Huang, Suiyuan; Magee, John C.; Alazraki, Adina; Freeman, A. Jay; Harned, Roger; Karmazyn, Boaz; Karnsakul, Wikrom; Leung, Daniel H.; Ling, Simon C.; et al.
Abstract : Objectives: Cystic fibrosis liver disease (CFLD) begins early in life. Symptoms may be vague, mild, or nonexistent. Progressive liver injury may be associated with decrements in patient health before liver disease is clinically apparent. We examined Health-Related Quality of Life (HRQOL) in children enrolled in a multi-center study of CFLD to determine the impact of early CFLD on general and disease-specific QOL. Methods: Ultrasound (US) patterns of normal (NL), heterogeneous (HTG), homogeneous (HMG), or nodular (NOD) were assigned in a prospective manner to predict those at risk for advanced CFLD. Parents were informed of results. We assessed parent/child-reported (age ≥5 years) HRQOL by PedsQL 4.0 Generic Core and CF Questionnaire-revised (CFQ-R) prior to US and annually. HRQOL scores were compared by US pattern at baseline (prior to US), between baseline and 1 year and at 5 years. Multivariate analysis of variance (MANOVA) with Hotelling-Lawley trace tested for differences among US groups. Results: Prior to US, among 515 participants and their parents there was no evidence that HTG or NOD US was associated with reduced PedsQL/CFQ-R at baseline. Parents of NOD reported no change in PedsQL/CFQ-R over the next year. Child-report PedsQL/CFQ-R (95 NL, 20 NOD) showed improvement between baseline and year 5 for many scales, including Physical Function. Parents of HMG children reported improved CFQ-R scores related to weight. Conclusions: Early undiagnosed or pre-symptomatic liver disease had no impact on generic or disease-specific HRQoL, and HRQoL was remarkably stable in children with CF regardless of liver involvement.